2015
DOI: 10.1007/s11442-015-1247-y
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover classification and its change detection using multi-temporal MODIS NDVI data

Abstract: Detailed analysis of Land Use/Land Cover (LULC) using remote sensing data in complex irrigated basins provides complete profile for better water resource management and planning. Using remote sensing data, this study provides detailed land use maps of the Lower Chenab Canal irrigated region of Pakistan from 2005 to 2012 for LULC change detection. Major crop types are demarcated by identifying temporal profiles of NDVI using MODIS 250 m  250 m spatial resolution data. Wheat and rice are found to be major crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 48 publications
2
56
0
1
Order By: Relevance
“…The cultivation of wheat, cotton and vegetables increased a lot especially because of promotion of precision land levelling and bed planting and drip irrigation (Tables 10 and 11). According to [42], the acreage under wheat and sugarcane during the Rabi season 2007-2008 was 497,214 hectares and 126,883 hectares, respectively, which was almost the same as reported in Table 8 for wheat and sugarcane. The acreage reported in Table 9 for rice, cotton, and sugarcane is in accordance with the area reported by [42] for rice, cotton and sugarcane during the Kharif season 2007 i.e., Rice cultivated area was 252,756 hectares, cotton cultivated area was 76,740 hectares and the sugarcane cultivated area was 198,419 hectares.…”
Section: Discussionsupporting
confidence: 63%
“…The cultivation of wheat, cotton and vegetables increased a lot especially because of promotion of precision land levelling and bed planting and drip irrigation (Tables 10 and 11). According to [42], the acreage under wheat and sugarcane during the Rabi season 2007-2008 was 497,214 hectares and 126,883 hectares, respectively, which was almost the same as reported in Table 8 for wheat and sugarcane. The acreage reported in Table 9 for rice, cotton, and sugarcane is in accordance with the area reported by [42] for rice, cotton and sugarcane during the Kharif season 2007 i.e., Rice cultivated area was 252,756 hectares, cotton cultivated area was 76,740 hectares and the sugarcane cultivated area was 198,419 hectares.…”
Section: Discussionsupporting
confidence: 63%
“…NDVI is a commonly used vegetation index in remote sensing, and it has been used extensively in land cover mapping (e.g. Rodrigues, Marcal, Furlan, Ballester, & Cunha, 2013;Usman, Liedl, Shahid, & Abbas, 2015). Previous studies reported that land use classification can also generally benefit from the incorporation of information from the red-edge part of the electromagnetic spectrum (e.g.…”
Section: Land Cover Mappingmentioning
confidence: 99%
“…For example, the Advanced Very High Resolution Radiometer (AVHRR) managed by the National Oceanic and Atmospheric Administration, possesses a coarse spatial resolution, while the Moderate Resolution Imaging Spectroradiometer (MODIS), Land Satellite (Landsat), and Advanced Space-borne Thermal Emission and Reflection Radiometer (ASTER) possess fine spatial resolutions. Specific advantages and disadvantages are associated with each type of them [34]. Due to the data volumes involved, the quality (i.e., season or cloud) as well as relatively low repeat times, the number of pre-collected medium spatial resolution images varies at different regions, thus provision of reliable and repeated urban information at regional to global scales remains a challenging task [35][36][37].…”
Section: Introductionmentioning
confidence: 99%